Haloperidol versus second-generation antipsychotics on the cognitive performance of individuals with schizophrenia and related disorders: pairwise meta-analysis of randomized controlled trials - Daniel Prates Baldez; Tais Boeira Biazus; Francisco Diego Rabelo-da-Ponte; Guilherme Pedro Nogaro; Dayane Santos Martins; João Pedro Soledade Signori; Vanessa Gnielka; Ives Cavalcante Passos; Letícia Sanguinetti Czepielewski; Maurício Kunz (Trends in Psychiatry and Psychotherapy)
Abstract Objective Despite previous literature, the superiority of second-generation antipsychotics (SGAs) relative to first-generation antipsychotics – especially haloperidol – on cognitive management in schizophrenia is still controversial. Thus, we aimed to compare the effects of haloperidol versus SGAs on the cognitive performance of individuals with schizophrenia or related disorders. Methods We conducted an updated systematic review and nine pairwise meta-analyses of double-blinded randomized controlled trials published up to October 30th, 2022, using MEDLINE, Web of Science, and Embase. Results Twenty-eight trials were included, enrolling 1,932 individuals. Compared to SGAs, haloperidol performed worse on cognitive composite (mean difference [MD] −0.13; 95% confidence interval [95%CI] −0.33 to −0.03), processing speed (MD −0.17; 95%CI −0.28 to −0.07), attention (MD −0.14; 95%CI −0.26 to −0.02), motor performance (MD −0.17; 95%CI −0.31 to −0.03), memory and verbal learning (MD −0.21; 95%CI −0.35 to −0.08), and executive function (MD −0.27; 95%CI −0.43 to −0.11). In contrast, there were no significant differences between SGAs and haloperidol on working memory (MD 0.10; 95%CI −0.08 to 0.27), visual learning (MD 0.08; 95%CI −0.05 to 0.21), social cognition (MD 0.29; 95%CI −0.30 to 0.88), and visuoconstruction (MD 0.17; 95%CI −0.04 to 0.39). Conclusion Haloperidol had poorer performance in global cognition and in some cognitive domains, but with small effect sizes. Therefore, it was not possible to conclude that haloperidol is certainly worse than SGAs in the long-term cognitive management of schizophrenia.